Using cement as filler to enhance asphalt mixes performance in hot climate regions - Aioub Guh; Gabriel Assaf (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper investigates the addition of different percentages of ordinary Portland cement as a filler in conventional asphalt concrete for a range of heavy traffic. Road pavement agencies in hot areas face the daunting challenge of preserving their pavements in a fair to good condition to increase their lifespan. This challenge is due to the high occurrence of permanent pavement deformation via rutting, which is one of the major distress factors influencing pavements. This is a particularly serious issue in hot and arid countries which are closely associated with various aggravating factors. These aggravating factors include the choice of bitumen binder viscosity, the type of bitumen, the available low-quality materials, and the high environmental temperatures. Ultimately, poor performance will show within the first few years of service as permanent deformations such as rutting, shoving, and depressions. The examined properties include the resilient modulus and the resistance to rutting. Findings indicate that the resistance to rutting and the rigidity of the asphalt concrete are both substantially increased as the cement content is increased. Moreover, to meet the heavy traffic spectrum requirements, increasing the embedded cement content in the asphalt concrete improves pavement structural capacity. Finally, based on the rigidity expected for different cement levels, design curves are provided for pavement design in hot climates using low quality aggregate materials.